The "blue bottle" experiment in the colloidal dispersions of smectites. (February 2021) - Šuteková, Monika; Bujdák, Juraj
Abstract: The Blue Bottle Experiment involves a reversible redox process of decolorizing methylene blue (MB) by reaction with glucose (Glc) at basic pH. The direction of the reaction is affected by the concentration of dissolved O2 . In this work, the reactions that took place in the presence and absence of nanoparticles of smectites (a group of layered silicates) were compared. The method of absorption spectroscopy with a diode-array detector was chosen for studying the reaction. It was possible to measure the full spectrum in a fraction of a second, and thus several hundred spectra were obtained for each experiment. Spectral matrices were analyzed using the chemometric method of multivariate curve resolution (MCR). Analysis of the results revealed not only the formation of known reaction products (a leuco-form of MB, the oxidation products of Glc) but also some other processes related to the changes of the reactants in a basic environment, slow dye decomposition, glucose isomerization, and the formation of MB molecular aggregates. The injection of colloidal smectite particles into the reaction system effectively stopped the redox reaction of MB with Glc, which may be important for dye stabilization in hybrid materials with smectites. This property was not related to the type of smectite, which instead affected the molecular aggregation occurring in the heterogeneous systems. Highlights: Blue bottle experiment is based on the reduction of methylene blue (MB) with glucose at high pH. The reaction was analyzed using UV–Vis spectroscopy and chemometric (MCR-ALS) methods. Layered silicate (saponite and montmorillonite) particles adsorbed MB and prevented the formation of leuco-form of MB. MB formed molecular aggregates on the surface of the silicates, but the dye was not reduced. Interpretations of spectral data and the role of the protective properties of the silicates are discussed.